Book Reviews (Historia, 2021)
1. Van Jaarsveld, F. A.: Die Ontwaking van die Afrikaanse Nasionale Bewussyn2. Wilkinson, B.: Constitutional History of Medieval England3. Ronda, Alexander: Geschiedenis der Mensheid4. Cottrel, Leonard: De Bergen van Pharao